Effect of Corn Starch and Glycerol Additions on the Characteristics of Capsule Shells from Seaweed Carrageenan - Ramadita, Aisha; Ariyanto, Hermawan Dwi (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Capsule shells are generally made by gelatinee which from animal based. However, the capsule shell has issues related to the permissibility (halalness) and safety. Carrageenan has the potential as an essential ingredient of the capsule shell to replace gelatinee. The focus of this study was to determine the optimal formulation for the preparation of capsule shells. There were 9 different formulations to test the best quality by comparing it with commercial capsule shells. The samples were manually moulded with a dipping pen for 3 s at 45℃. The concentrations of corn starch were 1%, 2%, and 3% w/v and concentration glycerol were 2%, 3%, and 4% w/v. Weight uniformity, specifications, disintegration, and FTIR were analysed to determine the best quality of the capsule shell. The results showed that formula with concentration of 95% of distilled water, 2% w/v of carrageenan, 2% w/v of corn starch and 3% w/v of glycerol fit the standard of capsule shell.